Kesalahan Morfologi dalam Karangan Narasi Siswa SMA Kelas XI Muhammadiyah Lamahala Adonara Timur Kabupaten Flores Timur - Rahman Muhamad; Rikardus Pande; Yoakim Yolanda Mario Leu (Social Science Academic, 2023)
This study aims to describe the forms of morphological affixation errors in students' narrative essays, especially prefixes, suffixes, infixes, and confixes. The subjects of this study were students of class XI SMA Muhammadiyah Lamahala. The data collected amounted to twenty narrative essays. The method used in this research is qualitative method . After the data is collected from the results of the analysis in written form. The analysis technique used is note-taking technique and reading technique. In composing narrative essays students are asked to write narrative essays in the form of personal experiences related to life stories both about family, friends, environmental conditions and others. The results of this study showed that of the twenty narrative essays analyzed, all students' narrative essays were obtained, namely the use of prefixes with 26 errors, 11 errors in the use of suffixes, and 3 errors in the use of confixes. Meanwhile, the use of infixes did not find errors.